2015
DOI: 10.1126/science.1261816
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional hierarchical self-assembly of amphiphilic cylindrical block comicelles

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms Abstract:Self-assembly of molecular and block copolymer amphiphiles represents a well-established route to micelles with a wide variety of shapes and gel-like phases. We demonstrate an analogous process, but on a longer lengthscale, in which amphiphilic P-H-P and H-P-H cylindrical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
412
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 466 publications
(415 citation statements)
references
References 39 publications
3
412
0
Order By: Relevance
“…In addition, the amphiphilicity of such block comicelles prior to the transformation of the B blocks would allow their self-assembly behavior to be explored in aqueous media. This might result in the formation of cylindrical micelle-based superstructures 59,82 with potential applications in tissue engineering or as stimuli-responsive biomaterials.…”
Section: Water-soluble B-a-b Multi-block Comicellesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the amphiphilicity of such block comicelles prior to the transformation of the B blocks would allow their self-assembly behavior to be explored in aqueous media. This might result in the formation of cylindrical micelle-based superstructures 59,82 with potential applications in tissue engineering or as stimuli-responsive biomaterials.…”
Section: Water-soluble B-a-b Multi-block Comicellesmentioning
confidence: 99%
“…[56][57][58][59][60] Herein, in an attempt to tackle the above-mentioned limitations, we report the preparation of well-defined, water-soluble cylindrical micelles of controlled length over a broad range up to 1.10 µm, with the added advantage of having a readily functionalizable coronaforming block. Furthermore, we report the first example of the formation of water-soluble cylindrical block comicelles.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] These techniques have been used to create hierarchical self-assembled structures and superstructures in solution. [13][14][15] Previous work on the liquid crystalline phase behaviour of PFS-based cylindrical micelles dispersed in decane revealed the existence of nematic and hexagonal phases, however discussion of the results was focussed predominantly on the isotropic and nematic phases. [7] Indeed where the phase behaviour of semi-flexible rods has been reported elsewhere, [16][17][18][19][20][21][22][23] there has been little discussion of what occurs at high concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…These structures were found to stack either side by side in non-solvents for the central block, or end to end in non-solvents for the terminal block, which allows the formation of a variety of 1D and 3D superlattice structures (see Figure 44). 378 These aggregates possess multiple levels of structural hierarchy on length-scales that are normally only apparent in nature. In addition, as the functionality of the micelle coronas is unchanged throughout the self-assembly process from the initial stages to the formation of superstructures.…”
Section: Formation Of Pfs Supermicelles By Hierarchical Self-assemblymentioning
confidence: 99%
“…377 As a continuation of this work on amphiphilic block comicelles, it was reported that the resulting micron-scale assemblies can be easily controlled through altering the dimensionality, functionality and ordering of the starting block comicelles. 378 Monodisperse BAB amphiphilic triblock comicelles with either hydrophilic or hydrophobic central or terminal blocks were prepared. These structures were found to stack either side by side in non-solvents for the central block, or end to end in non-solvents for the terminal block, which allows the formation of a variety of 1D and 3D superlattice structures (see Figure 44).…”
Section: Formation Of Pfs Supermicelles By Hierarchical Self-assemblymentioning
confidence: 99%